Theoretical modal characteristics of integral abutment bridge with bored piles foundation - Ibrahim, Muhammad Khairil (2015)
Since 2008, the Public Works Department of Malaysia had adopted the integral abutment bridge concept as one of the initiatives to reduce the maintenance costs of bridges. Although this type of bridge is popular in the developed country such as United States, United Kingdom and Japan, the use of integral bridges in the South East Asia Country is considered relatively new. While most of the researches focussed on theoretical dynamic characteristic of bridge founded with H-piles, this paper presents the theoretical dynamic characteristics of integral bridge abutment with bored piles determined by the FE modal analysis performed by using ABAQUS software. A single-span integral bridge located in Pahang, Malaysia has been selected as the case study. The modal characteristics of the same design of bridge with simply supported bridge yield different values of modal frequency, which are higher. From the FE modelling result, it was found that the integral bridge with the bored piles type of foundation possess lower natural frequencies compared to the simply supported bridge of similar type of foundation.